Analysis of Ability to Write Essay Description Using Illustrated Image Media on Class V Students - Simayang, Era; Sunarsih, Eti; Hendriana, Evinna Cinda; Xiaontian, Xiaontian (International Journal of Multi Discipline Science (IJ-MDS), 2024)
This study aims to (1) describe students' ability to write descriptive essays using illustrations as media. (2) describe students' responses in writing descriptive essays. The type of research used is qualitative research with a descriptive approach. The subjects studied in this study were 17 fifth-grade students at SDN 84 Singkawang. The use of media during learning is important to support student's ability to achieve learning goals. This study aims to describe students' abilities in writing descriptive essays using illustration media, as well as to find out students' responses in writing descriptive essays using illustration media. Results showed that the results of the ability to write descriptive essays showed that 29% of the ability to write descriptive essays was in the very good category, 53% of the ability to write descriptive essays was in the good category, and 18% of the ability to write descriptive essays was in the sufficient category. From the results of the ability to write descriptive essays per indicator, an average score of 79 is obtained in the good category. From the results of the responses obtained 12% of student responses in the very good category, 88% of student responses in the good category, and from the results of the distribution of response levels obtained an average value of 75.8 in the good category. Thus it can be concluded that the ability to write descriptive essays using illustration media and student responses to the illustrated media used in writing descriptive essays is good.